IMPLEMENTATION OF THE INTEGRATED MANAGEMENT SYSTEM IN THE NUCLEAR SECTOR IN ACCORDANCE WITH INTERNATIONAL ISO STANDARDS AND THE REQUIREMENTS OF THE INTERNATIONAL ATOMIC ENERGY AGENCY (British Journal of Global Ecology and Sustainable Development, 2023)
Nuclear Materials Authority seeks to create an integrated management system where (IMS) is becoming increasingly important for nuclear organizations, the interest in this topic means that IMS is seen as the future management system.